The Contemporary Critical Reception of Walter Pater: Retrospective and Proleptical Views - Geoffrey Sadock (Cahiers Victoriens et Edouardiens)
Since the advent of the Computer Age, there has been a veritable explosion in late Victorian studies in general and in Pater studies in particular. While it is true that he was still somewhat under a cloud in the early 1970s, that cloud has dissipated. In November 2005, for example, there were 109,000 hits on him on the Internet. Whole schools of thought have arisen about the man and his oeuvre. Leading scholars have devoted the better part of their professional lives to him and have become far more reliable and candid authorities than any who wrote between the 1860s and the 1970s.It is high time for scholars concerned about his literary reputation to assess 20th and 21st century perceptions of Pater, to elucidate his continuing hold on the modern literary imagination, and to review the critical tradition of the last 35 years. This paper attempts to do just that. By showing the shift from hostile modernism to a more open and inclusive conception of his literary persona, I explain why Pater is no longer dismissed as precieux and inconsequential by the guardians of High Culture (such as Eliot) but is recognized as an original who synthesized personal preoccupations and aesthetic/critical response to various art forms, nature, and persons. Since Western culture no longer upholds the restrictions under which Pater labored to define his Weltanschauung, his genius in the use of suggestion—association, transparency, diaphaneity, masochistic delay—has become more recognizable. The hallmark of a master craftsman is that he can keep the rules of his genre or Sitz im Leben, but, because he has thoroughly internalized those rules, make his performance appear graceful, even spontaneous. In this regard, Pater has few equals. No longer burdened with the need to condemn his orientation, desire, or lifestyle, recent critics can readily appreciate the subtlety with which Pater interweaves intellectual history, aesthetic method, and sensual self-indulgence. What scandalized some of his contemporaries and those who considered him, however dismissively, in the middle of the 20th century, can now be regarded as an aspect of what Lawrence S. Kubie called the neurotic distortion of the creative process, a distortion born primarily of intolerance and repression.The last part of the essay explains why, as inclusion and acceptance gain ground in the wider culture, Pater will be found more relevant and interesting. His foundational affirmation of the modern spirit, relativism linked with sensual exploration, will seem more congenial to 21st century readers than it did to those grounded in a ‘facile orthodoxy.’ As Pater’s response to the beautiful, in art and life, becomes better understood, it will be seen that he is at once the culmination of a long line of theoretical rebels and the beginning of a post-modern, existential methodology that values art after the debacle of the 20th century and the collapse of ideologies that once sought to discredit him. He will then assume the stature to which he is entitled.